Environmental sustainability of grey water footprints in Peshawar Basin: Current and future reduced flow scenarios for Kabul River - Khan, Tariq; Khan, Hizbullah (International Journal of Agricultural and Biological Engineering, 2019)
Assessing water pollution at basin level is a challenging task. In this study, the environmental sustainability of grey water footprints (WFgrey) of Peshawar Basin in Pakistan was analysed. The release of nitrogen (N) and phosphorus (P) from point and non-point sources during the period 1986 to 2015 were studied. Water pollution level (WPL) for normal and 10%-50% future reduced runoff in Kabul River as a result of construction of dams was considered. Methodologies described in Water Footprint Assessment Manual and Grey Water Footprint Accounting Guidelines were followed. Results showed that 30-year annual average of N and P discharges were 24.5×103 t/a and 10.9×104 t/a respectively. The discharge of N and P from non-point sources contribute 97% and 99% respectively. N related WFgrey was 50108 m3/a and 50109 m3/a for P. WPL of N was within the sustainable limit for all reduced runoff scenarios while P-related WPL for normal runoff exceeded sustainable limits and was worse in each reduced runoff scenario. This study confirms the deteriorated water quality of Kabul River and the findings may be helpful for future planning and water resource management of the basin. Keywords: sustainability, grey water footprint, nitrogen, phosphorus, water pollution, Kabul River, Pakistan DOI: 10.25165/j.ijabe.20191204.4804 Citation: Khan T, Khan H. Environmental sustainability of grey water footprints in Peshawar Basin: Current and future reduced flow scenarios for Kabul River. Int J Agric & Biol Eng, 2019; 12(4): 162–168.